Germany's defeat in the First World War - Karau, Mark D., 1969- (Santa Barbara, California)
xiv, 212, [1] s.
Keywords: "Much has been written about the causes for the outbreak of World War I and the ways in which the war was fought, but few historians have tackled the reasons why the Germans, who appeared on the surface to be winning for most of the war, ultimately lost. This book, in contrast, presents an in-depth examination of the complex interplay of factors—social, cultural, military, economic, and diplomatic—that led to Germany's defeat. The highly readable work begins with an examination of the strengths and weaknesses of the two coalitions and points out how the balance of forces was clearly on the side of the Entente in a long and drawn-out war. The work then probes the German plan to win the war quickly and the resulting campaigns of August and September 1914 that culminated in the devastating defeat in the First Battle of the Marne. Subsequent chapters discuss the critical factors and decisions that led to Germany's loss, including the British naval blockade, the role of economic factors in maintaining a consensus for war, and the social impact of material deprivation." --